2013
DOI: 10.1116/1.4820493
|View full text |Cite
|
Sign up to set email alerts
|

Critical review: Effects of complex interactions on structure and dynamics of supported metal catalysts

Abstract: This review article takes a new look at the problem of characterization of structural properties and reaction dynamics of supported metal catalysts. Such catalysts exhibit an inherent complexity, particularly due to interactions with the support and the adsorbate molecules, which can be highly sensitive to environmental conditions such as pressure and temperature. Recent reports demonstrate that finite size effects such as negative thermal expansion and large bond length disorder are directly caused by these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 262 publications
(262 reference statements)
1
27
0
Order By: Relevance
“…[40] Moreover, a recent study of γ-Al 2 O 3 -supported Pt particles with an average diameter of 1 nm demonstrated a Pt–Pt bond length contraction at elevated temperatures. [41] The largest rhodium particles were observed for zirconiated rhodium catalysts throughout CO exposure at the temperatures studied. These results suggest that Zr species are in intimate contact with Rh entities to form larger Rh particles under H 2 /He at 323 K, which consequently protects them against oxidative disruption upon exposure to CO/He.…”
Section: Resultsmentioning
confidence: 99%
“…[40] Moreover, a recent study of γ-Al 2 O 3 -supported Pt particles with an average diameter of 1 nm demonstrated a Pt–Pt bond length contraction at elevated temperatures. [41] The largest rhodium particles were observed for zirconiated rhodium catalysts throughout CO exposure at the temperatures studied. These results suggest that Zr species are in intimate contact with Rh entities to form larger Rh particles under H 2 /He at 323 K, which consequently protects them against oxidative disruption upon exposure to CO/He.…”
Section: Resultsmentioning
confidence: 99%
“…Metal-support interactions play a pivotal role in the performance of supported catalysts [148][149][150] by not only enhancing stability, but also by endowing improved catalytic properties such as significantly enhanced catalytic activities and selectivity due to altered electronic structures or synergetic catalytic effects [2,[151][152][153][154]. And in SACs, this effect is more pronounced and is a determining factor in the performance of SACs due to contact between isolated metal atoms and supports [155].…”
Section: The Anchoring Mechanismmentioning
confidence: 99%
“…A useful tool for unlocking this relationship is an operando experiment, in which changes in structural and chemical features are measured simultaneously with the catalytic activity [25][26][27] . However, the small amount of active component in dilute alloys, compounded with low weight loading of the particles, require characterization tools with sufficient surface and chemical sensitivities.…”
mentioning
confidence: 99%